2019
DOI: 10.3390/ani9090681
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 13 bp Deletion within the NR6A1 Gene Is Significantly Associated with Growth Traits in Donkeys

Abstract: Simple SummaryThe detection of genes potentially associated with economic traits and identification of effective variants can provide a basis for molecular marker-assisted selection of livestock. NR6A1 is a member of the nuclear receptor family and is an important candidate gene related to body size traits. Previous studies showed that NR6A1 gene was associated with body size traits in pigs and other livestock, however, it has not yet been observed in donkeys. In the current study, a 13 bp deletion in NR6A1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…As a first-class candidate gene, NR6A1 has been studied in several animals and association with the vertebrae number has been proved. Fang et al detected a 13 bp Indel in the intron 1 of the Dezhou donkey NR6A1 gene, and found it was significantly associated with growth traits [ 35 ]. Zhang et al [ 12 ] found that there was a significant association between SNV (rs414302710: A > C) in the exon-8 of NR6A1 gene with the number of lumber vertebrae in sheep ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…As a first-class candidate gene, NR6A1 has been studied in several animals and association with the vertebrae number has been proved. Fang et al detected a 13 bp Indel in the intron 1 of the Dezhou donkey NR6A1 gene, and found it was significantly associated with growth traits [ 35 ]. Zhang et al [ 12 ] found that there was a significant association between SNV (rs414302710: A > C) in the exon-8 of NR6A1 gene with the number of lumber vertebrae in sheep ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Marker-assisted selection (MAS) has been widely used in breeding. The application of DNA markers for improving growth traits through MAS is a more efficient and powerful tool than the traditional method [18,19]. Therefore, this study aimed to reveal the significant genetic variations in the bovine RET gene and investigate the relationship between genotypes and body measurement in two Chinese cattle breeds, Qinchuan cattle (QC) and Nanyang cattle (NY).…”
Section: Introductionmentioning
confidence: 99%
“…By combining haplotype combinations with single locus effects, the effects of genetic variation can be more easily demonstrated (Gui et al, 2015). It can be seen from Tables 4 and 5 that the results of haplotype combination analysis and unit point analysis of the mutation site of the ACSL1 gene are consistent.…”
Section: Discussionmentioning
confidence: 80%